Is the expression of different discrete emotions related to time? Evidence from online Chinese reviews using sentiment analysis and human behavior dynamics - Li-na, Liu; Jia-yin, Qi; Sheng-feng, Wang; Zhen-ping, Zhang; Qi-xing, Qu (Frontiers in Psychology, 2024)
[Objectives]The online behavior of online users has taken on complex and diverse characteristics, and posting product reviews on e-commerce platforms is no exception. In fact, reviews contain rich and multi-dimensional discrete emotional information, and whether there is a relationship between the expression of these different discrete emotions and the time interval between product purchase and review posting, and what related characteristics are the issues that this study needs to analyze and solve in depth.[Methods]Based on the OCC model of psychological emotional cognitive evaluation theory as the basis for emotion classification, the study used the massive Chinese reviews of mobile on the large Chinese e-commerce platform Jingdong Mall as the research object, and applied supervised machine learning methods to classify discrete emotions and constructed a large corpus containing satisfaction, disappointment, admiration, reproach, like and hate, and then the study delved into the distribution and behavioral dynamics characteristics of consumers' comments containing different discrete emotions at different "purchase-comment" time intervals.[Results]The results show that the first peak of the distribution curves of the six discrete emotions at different "purchase-comment" time intervals occurs on the first day after purchase, and then decreases gradually, but at different rates. The three curves for satisfaction, love and hate emotions also show a second peak on the eleventh day, which is more similar to the bimodal distribution, implying that the corresponding product reviews are more objective. In addition, the distribution of reviews containing the six discrete emotions at different "purchase-comment" time intervals follows a power-law distribution and has the temporal characteristics of Human Behavioral Dynamics -"strong paroxysms and weak memory ".However, the reviews containing the admiration and reproach emotions were most intensively written by consumers after the purchase, indicating that the service provided by the seller, logistics and e-commerce platform stimulates more consumers to give quick responses and detailed reviews.[Conclusions]This study is not only of great significance for exploring the internal mechanisms of consumer discrete emotional expression, but also provides important decision-making references for potential consumer purchasing decisions, product updates for developers, marketing strategy formulation for marketing teams, and service improvement for sellers, logistics companies, and ecommerce platforms.